Analisis Kualitas Pelayanan Perizinan Berdasarkan Metode Servqual Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Karimun - Bagas Rifqi Hanindya; Budi Astuti (SAFE-Network, 2023)
This descriptive qualitative type of research aims to find out the quality of service at the Karimun Regency DPMPTSP. Primary data was obtained from interviews and observations from the research location. The approach used in this research is the servqual method with five dimensions, namely: physical evidence, reliability, responsiveness, assurance, and empathy. The results of the report show that the quality of licensing services at DPMPTSP Karimun Regency is quite good. This is proven from the results of interviews and observations which state physical evidence (requirements and infrastructure), reliability (systems, mechanisms and procedures as well as implementing competence), responsiveness (time for resolving and handling complaints, suggestions and input), assurance (costs/tariffs and product specifications, type of service), and empathy (executor's behavior) are important factors that have a positive and satisfying effect on customers who use the services at this agency.